1998
DOI: 10.1021/ma9804139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and X-ray Characterization of Alkoxy-Substituted Aromatic Polyesters Containing Terphenyl or Quinquephenyl Units in the Main Chain

Abstract: Soluble aromatic polyesters derived from 2′,5′-dialkoxy-p-terphenyl-4,4′-diols or 2′′,5′′didodecyloxy-p-quinquephenyl-4,4′′′′-diol and terephthaloyl or 2,5-dialkoxy-terephthaloyl dichlorides were prepared. The polymers were characterized by viscosimetry, thermal analysis, and X-ray diffraction. The polyesters show two or more endothermic transitions. The high-temperature transitions to an isotropic melt moved to lower temperatures as the side chain length increased. Structural information was obtained from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…More particularly, alkoxy-substituted polymers show a significant tendency towards self-organization in a supramolecular level starting from the ''hairy-rod'' polymers, where the lateral attachment of alkoxy-substituents onto a rigid or semi-rigid polymeric backbone resulted in the formation of layered structures with different characteristics depending on the length of the side chains and the substitution density. [4][5][6][7][8] Additionally, alkoxy periphery decorated dendrons and dendrimers have revealed assemblies formed due to the Summary: Rigid-flexible polyethers consisting of terphenyl and aliphatic segments of various lengths along their main chains and disubstituted by dendritic wedges of various generations (G 0 , G 1 , and G 2 ) are examined in their bulk states. Characterization of phase transitions has been performed by means of differential scanning calorimetry (DSC) and was supported by structural information obtained from smallangle light scattering (SALS) and polarized optical microscopy (POM) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…More particularly, alkoxy-substituted polymers show a significant tendency towards self-organization in a supramolecular level starting from the ''hairy-rod'' polymers, where the lateral attachment of alkoxy-substituents onto a rigid or semi-rigid polymeric backbone resulted in the formation of layered structures with different characteristics depending on the length of the side chains and the substitution density. [4][5][6][7][8] Additionally, alkoxy periphery decorated dendrons and dendrimers have revealed assemblies formed due to the Summary: Rigid-flexible polyethers consisting of terphenyl and aliphatic segments of various lengths along their main chains and disubstituted by dendritic wedges of various generations (G 0 , G 1 , and G 2 ) are examined in their bulk states. Characterization of phase transitions has been performed by means of differential scanning calorimetry (DSC) and was supported by structural information obtained from smallangle light scattering (SALS) and polarized optical microscopy (POM) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a great deal of effort has been expended to try to improve the processing characteristics of the relatively intractable polymers. [2][3][4][5][6][7][8][9][10][11] Introduction of pendent loops along the polymer backbone has been shown to impart greater solubility and enhanced rigidity as well as better mechanical and thermal properties to the resulting cardo polymer, which is of particular importance in aromatic heterocyclic polymers with rigid chains. 12 It has been reported that the presence of cardo groups such as fluorene, phthalide, phthalimidine, and anthrone in the repeat unit of polyester results in enhanced solubility as well as high thermal properties of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…DMF was distilled under reduced pressure and stored over molecular sieves. 2-Amino-5-bromobenzophenone (29, 34), 2-tetrahydropyranyloxy-4-phenylboronic acid (35), 2,5-bis(didodecyloxy) phenylene-1,4-diboronic acid (36), tetrakis (triphenylpshosphine) palladium (0) (Pd(PPh 3 ) 4 ) (37) were synthesized according to literature methods. 1,12-Dibromododecane was recrystallized from methanol.…”
Section: Materials and Instrumentationmentioning
confidence: 99%